1991
DOI: 10.1111/j.1600-0528.1991.tb00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental fear and anxiety in an older adult population

Abstract: A random sample of 580 people aged between 50 and 89 yr completed a questionnaire containing two measures of dental fear and anxiety. One of these was Corah's Dental Anxiety Scale (DAS) and the other a scale derived from the Structured Interview for Assessing Dental Fear (SIADF). The mean score on the DAS was 7.8, and 8.4% of subjects were classified as dentally anxious. There were no differences in mean DAS scores by sex but significant differences by age, with younger individuals having higher scores (P less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
66
4
10

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 18 publications
14
66
4
10
Order By: Relevance
“…High anxiety (DAS = 13-20) was experienced by 36 (6.15%). This was not consistent with the results of other studies which found a considerably greater percentage of students with dental anxiety (2,6,10,11,13) and that women are more prone to experience dental fear than men are. In our study we found no difference between the two genders.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…High anxiety (DAS = 13-20) was experienced by 36 (6.15%). This was not consistent with the results of other studies which found a considerably greater percentage of students with dental anxiety (2,6,10,11,13) and that women are more prone to experience dental fear than men are. In our study we found no difference between the two genders.…”
Section: Discussioncontrasting
confidence: 55%
“…These conditions occur in people of any age and social status. Statistics show that it is the 25-26-year-olds that tend to experience higher dental anxiety than other people (9)(10)(11). This can be accounted for by the diverse effects of a number of psychological factors in this age range that can induce dental fear and dental anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with the study conducted by Özdemir et al (2). However, the results of other studies conducted in Turkey and in other countries indicated that women have more fear and anxiety of dental treatment than men (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Discussioncontrasting
confidence: 40%
“…The response rate of 14% was admittedly low although as argued immediately above we believe the potential bias was minimal. Other authors using telephone survey techniques also experienced similar problems (with an 18.5% response rate) and use identical arguments to our own to support the veracity of the data set [28]. However, a risk of sampling bias exists with telephone survey methods if response rates vary in different groups within a population.…”
Section: Discussionmentioning
confidence: 87%
“…The mean dental anxiety scores for those aged 60 and above were higher in males in the current survey compared to the original community sample (page 147; table five, males: mean = 7.52 (3.81) n = 122 versus 6.52 (2.34) n = 50; t = 2.17, df = 170, p = .016), whereas females showed a smaller increase in the recent survey compared to the original, and the difference was not significant: 10.09 (5.57) n = 122 versus 9.23 (5.25) n = 71; t = 1.07, df = 191, p = .146). There is partial support therefore for Locker's suggestion [28] that the 50-59 year old cohort 'will carry their relatively high levels of dental anxiety into old age' [29]. This effect appears to be shown in males only.…”
Section: Discussionmentioning
confidence: 92%